2016
DOI: 10.3390/polym8120433
|View full text |Cite
|
Sign up to set email alerts
|

Study on Hydrogen Sensitivity of Ziegler–Natta Catalysts with Novel Cycloalkoxy Silane Compounds as External Electron Donor

Abstract: Two novel cycloalkoxy silane compounds (ED1 and ED2) were synthesized and used as the external electron donors (EEDs) in Ziegler-Natta catalysts with diethyl 2,3-diisopropylsuccinate as internal electron donor. The results indicated that the Ziegler-Natta catalysts using ED1 and ED2 as EEDs had high catalytic activities and good stereoselectivities. The melt flow rate (MFR) and gel permeation chromatography (GPC) results revealed that the obtained polypropylene has higher MFR and lower average molecular weight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 33 publications
0
6
0
Order By: Relevance
“…Generally, polymers with high molecular weight have stronger intermolecular interaction, which causes low MFR and higher viscosity [34]. Whereas, polymers with high MFRs often feature low molecular weight or broad molecular weight distribution [8]. Changes in MFR values of polymers influence the properties of fibres, such as elongation and bond strength.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Generally, polymers with high molecular weight have stronger intermolecular interaction, which causes low MFR and higher viscosity [34]. Whereas, polymers with high MFRs often feature low molecular weight or broad molecular weight distribution [8]. Changes in MFR values of polymers influence the properties of fibres, such as elongation and bond strength.…”
Section: Resultsmentioning
confidence: 99%
“…Consequently, compatibilization agents are essential for their production. Melt flow rate (MFR), which is the processability of a polymer, is considered important in PP manufacturing; whereas, PP products with high MFR are easy to process and also boost production speed [8]. Li et al also reported that highly desirable iPP with high MFR is schematised for production by 2025 in China.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Highly hydrogen-sensitive Ziegler–Natta catalysts have become among the most important aspects of polyolefin catalyst research. The higher the hydrogen sensitivity of the catalyst, the better the control of molecular weight and its distribution in a larger range . In order to evaluate the effect of novel internal electron donors on the hydrogen regulation sensitivity of the catalyst, propylene polymerization at three different concentrations of H 2 was performed.…”
Section: Resultsmentioning
confidence: 99%
“…The higher the hydrogen sensitivity of the catalyst, the better the control of molecular weight and its distribution in a larger range. 31 In order to evaluate the effect of novel internal electron donors on the hydrogen regulation sensitivity of the catalyst, propylene polymerization at three different concentrations of H 2 was performed. Cat.5 was selected to explore its hydrogen sensitivity under different hydrogen conditions, and the results of corresponding polymerization are summarized in Table 5.…”
Section: The Composition Analysis Of Catalystsmentioning
confidence: 99%